Novel quorum sensing inhibitor Echinatin as an antibacterial synergist against Escherichia coli - Bai, Yu-Bin; Shi, Meng-Yan; Wang, Wei-Wei; Wu, Ling-Yu; Bai, Yu-Ting; Li, Bing; Zhou, Xu-Zheng; Zhang, Ji-Yu (Frontiers in Microbiology, 2022)
A new antibacterial strategy based on inhibiting bacterial quorum sensing (QS) has emerged as a promising method of attenuating bacterial pathogenicity and preventing bacterial resistance to antibiotics. In this study, we screened Echinatin (Ech) with high-efficiency anti-QS from 13 flavonoids through the AI-2 bioluminescence assay. Additionally, crystal violet (CV) staining combined with confocal laser scanning microscopy (CLSM) was used to evaluate the effect of anti-biofilm against Escherichia coli (E. coli). Further, the antibacterial synergistic effect of Ech and marketed antibiotics were measured by broth dilution and Alamar Blue Assay. It was found that Ech interfered with the phenotype of QS, including biofilm formation, exopolysaccharide (EPS) production, and motility, without affecting bacterial growth and metabolic activity. Moreover, qRT-PCR exhibited that Ech significantly reduced the expression of QS-regulated genes (luxS, pfs, lsrB, lsrK, lsrR, flhC, flhD, fliC, csgD, and stx2). More important, Ech with currently marketed colistin antibiotics (including colistin B and colistin E) showed significantly synergistically increased antibacterial activity in overcoming antibiotic resistance of E. coli. In summary, these results suggested the potent anti-QS and novel antibacterial synergist candidate of Ech for treating E. coli infections.